Phylum Gemmatimonadota and Its Role in the Environment - Mujakić, Izabela; Piwosz, Kasia; Koblížek, Michal (Microorganisms, 2022)
Bacteria are an important part of every ecosystem that they inhabit on Earth. Environmental microbiologists usually focus on a few dominant bacterial groups, neglecting less abundant ones, which collectively make up most of the microbial diversity. One of such less-studied phyla is Gemmatimonadota. Currently, the phylum contains only six cultured species. However, data from culture-independent studies indicate that members of Gemmatimonadota are common in diverse habitats. They are abundant in soils, where they seem to be frequently associated with plants and the rhizosphere. Moreover, Gemmatimonadota were found in aquatic environments, such as freshwaters, wastewater treatment plants, biofilms, and sediments. An important discovery was the identification of purple bacterial reaction centers and anoxygenic photosynthesis in this phylum, genes for which were likely acquired via horizontal gene transfer. So far, the capacity for anoxygenic photosynthesis has been described for two cultured species: Gemmatimonas phototrophica and Gemmatimonas groenlandica. Moreover, analyses of metagenome-assembled genomes indicate that it is also common in uncultured lineages of Gemmatimonadota. This review summarizes the current knowledge about this understudied bacterial phylum with an emphasis on its environmental distribution.
Keywords: anoxygenic photosynthesis; photosynthetic gene cluster; Gemmatimonadota; MAGs; Gemmatimonadetes